Impact of Viral Inflammation on the Expression of Renal Drug Transporters in Pregnant Rats - Navaz Karimian Pour; Eliza R. McColl; Micheline Piquette-Miller (MDPI AG, 2019)
Inflammation impacts the expression and function of drug transporters at term-gestation; however, the impact of inflammation on the expression of drug transporters at mid-gestation is largely unknown. Since renal drug transporters play a key role in the clearance of many drugs prescribed during pregnancy, our objective was to study the impact of the viral mimetic poly I:C on the expression of renal transporters in pregnant rats at mid-gestation. Poly I:C (10 mg/kg) or saline was administered intraperitoneally to pregnant Sprague−Dawley rats on gestational day 14. Expression of renal transporters was measured at 6, 24, and 48 h by qRT-PCR and Western blot. The mRNA levels of Mdr1a, Mrp4, Oct2, Octn1, Octn2, Mate1, Oat1-3, Urat1, Oatp4c1, Ent1, and Pept2 were significantly lower in the poly I:C group at 6 h. At 24 h, only the mRNA levels of Oct2, Oatp4c1, and Ent1 were decreased compared to saline. Poly I:C significantly decreased protein expression of Urat1 at 24 h, and P-gp, Oct2, Mate1, Oat1, Oat3 at 48 h,. Poly I:C imposed significant reductions in the expression of several key renal transporters at mid-gestation in pregnant rats. Thus, viral infection may impact renal excretion of drug transporter substrates, potentially leading to drug−disease interactions.